SUB-EPITHELIAL CONNECTIVE TISSUE GRAFT COMBINED WITH PLATELET-RICH FIBRIN IN MANAGEMENT OF PERI-IMPLANT SOFT TISSUE DEHISCENCE – A CASE REPORT - Dr. MM Dayakar, Dr Shivani Kumari, (EPRA International Journal of Research and Development (IJRD), 2023)
Over the past 2 decades the use of dental implants to advance functional and esthetic demands of dentition has amplified significantly. Patients today have become extremely concerned about esthetics which has become an integral part of the periodontal practice. One of the major factors contributing to improved esthetics is soft and hard tissue management. A chief esthetic concern is soft tissue defects around implant restoration. Implant soft tissue dehiscences compromise the aesthetics of the supported restorations and also implant survival in the long run. The present case report gives a novel technique for soft tissue reconstruction and covering defects associated with a palatally placed maxillary implant-supported restoration. A pedicle subepithelial connective tissue graft was prepared from the palatal mucosa and was displaced into the receptor site, along with the PRF. The receptor and donor site were primarily covered. After surgery of four months, the peri-implant soft tissue margin was compared with the baseline. A 2 mm increase in buccal soft tissue margin was accomplished. There was good stability of the soft tissue margin and the esthetic appearance of the implant site was well preserved. This case report demonstraes the possibility of fully correcting peri-implant soft tissue defects and achieving high patient satisfaction through a subepithelial connective tissue graft in conjunction with growth factors.